The Effect of TikTok Affiliate Income on Personal Financial Budget Management Among Students with Financial Literacy as a Mediating Variable - S, Nadila.; Basri Basir; Wahyuni, Wahyuni (Economos : Jurnal Ekonomi dan Bisnis, 2026)
This study aims to analyze the effect of TikTok Affiliate income on students personal financial budget management, with financial literacy as a mediating variable. The study used a quantitative approach with a survey method of students from the Faculty of Economics & Business, Muhammadiyah University of Makassar class of 2022 who participated in the TikTok Affiliate program. Data were collected through questionnaires and analyzed using linear regression and the Sobel mediation test with the help of SPSS. The results show that TikTok Affiliate income and financial literacy have a positive and significant effect on students' personal financial budget management, and financial literacy can mediate the effect of TikTok Affiliate income. These findings suggest that student financial management will be more optimal if increased digital income is supported by good financial literacy.